THE EFFECT OF THE IMPLEMENTATION OF GREEN SUPPLY CHAIN MANAGEMENT PRACTICES ON THE SUSTAINABILITY PERFORMANCE AND OPERATIONAL COMPETITIVENESS OF THE COLD SUPPLY CHAIN: QUANTITATIVE EVIDENCE FROM PT. CIMORY AND ITS LOGISTICS PARTNERS - Sri Wahyuni; Syahrum Agung; Zakie Hanifan (RADJA PUBLIKA, 2026)
The transition to a green economy puts significant pressure on the cold supply chain industry, which is inherently energy-intensive. The integration of Green Supply Chain Management (GSCM) is thought to be a strategic solution, but quantitative empirical evidence on its impact on sustainability performance and operational competitiveness in the context of cold chain in Indonesia is still limited. Objective: This study aims to examine the influence of the implementation of GSCM practices on sustainability performance (triple bottom line) and operational competitiveness in the cold supply chain of PT. Cimory and its network of logistics partners. Method: Explanatory quantitative research was conducted by distributing questionnaires to 150 managerial respondents from PT. Cimory and its main logistics partners. The data was analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test the relationships between variables. Findings: The results of the study prove that the implementation of GSCM practices has a positive and significant effect directly on improving sustainability performance (β=0.487; p<0.001) and operational competitiveness (β=0.352; p<0.01). The novel findings reveal that sustainability performance plays a role as a partial mediator that strengthens the influence of GSCM on operational competitiveness. Newness: This study contributes contextual quantitative evidence of integrated cold chain networks in the Indonesian perishable products industry, as well as clarifies the mediation mechanisms among key variables